Magnesium, phosphate, and calcium supplementation and human physical performance - Lukaski, H. C. (Macroelements, Water, and Electrolytes in Sports Nutrition, 1999)
There is increasing interest in the roles played by magnesium, phosphate and calcium in the development and enhancement of physical performance by athletes and physically active individuals. This interest is sparked by knowledge that magnesium and phosphate are needed for energy production by cells, and calcium plays a key role in maintenance of bone mass and possible prevention of injuries. Support for generalized magnesium supplementation is low unless individuals have decreased cellular magnesium. Acute and chronic supplementation with phosphate compounds does not increase physical work capacity or endurance in humans. Low calcium intake can predispose active individuals to lingering problems with bone stress injuries. Apparently daily calcium intakes of at least 800 milligrams per day are adequate to maintain adequate bone mass. The routine use of magnesium, phosphate and calcium supplements does not enhance performance or function in people who consume diets that contain these nutrients in amounts that equal the recommended daily intakes. This information will be useful to dietitians who advise physically active people.